Occurrence, Distribution and Contamination Levels of Heavy Metals and Phenolic Endocrine-Disrupting Chemicals in Water, Sediment, and Oreochromis niloticus (TILAPIA) in Bonny River, Nigeria - Boma, M, Nwoke, I. B, (American Journal of Biology and Natural Sciences, 2026)
This study investigated the concentrations of some heavy metals and phenolic endocrine-disrupting chemicals (EDCs) in surface water, sediment, and biota in the creeks and rivers around Bonny River, Rivers state, Nigeria. Water and sediment samples were collected from four (4) different sampling locations along the river, while the biota (tilapia) was bought from local fishermen along the river banks. The samples were prepared and analyzed for heavy metals using Atomic Absorption Spectrophotometer, and the samples for EDCs were analyzed using Gas chromatograph – Mass Selective detector system (GC/MS). The data obtained were further subjected to index models (Contamination factor and Pollution load index) of heavy metals. The results from the detectable concentrations (mg/l) for heavy metals in water were: Pb (3.23 ± 1.11), Cd (0.05 ± 0.06), Cr (3.67 ± 1.48), Ni (0.14 ± 0.16), As (0.28 ± 0.24), and V (0.01 ± 0.01). Heavy metals concentration (mg/kg) in sediment were: Pb (7.59 ± 3.17), Cd (0.15 ± 0.12), Cr (9.33 ± 3.84), Ni (2.39 ± 1.98), As (0.96 ± 0.83), and V (0.08 ± 0.10). The results from the detectable concentrations (mg/l) for heavy metals in biota were: Pb (1.07 ± 0.00), Cd (0.46 ± 0.12), Cr (1.36 ± 0.20), Ni (0.36 ± 0.06), As (0.38 ± 0.05), and V was below detection limit (BDL < 0.001). The results, on comparison with international and local standards (WHO, NIS, EPA) revealed that all the heavy metals analyzed in water were above the limits, except for V in water. In sediment, all the heavy metals analyzed were below the limits, and in fish, metals Pb and Cd were above the limits, Cr, Ni, and As were below the limits, and V was undetected. The mean concentration (µg/l) of EDCs in water was 34.08 ± 22.21, in sediment was 51.84 ± 33.61, and in biota recorded 23.98 ± 13.75. The contamination factor for water shows that there is very high degree of contamination of Pb, Cd, Cr, and As, with moderate degree of contamination for Ni and V. No degree of contamination was seen for sediments, and in biota, moderate degree contamination was seen for Pb and Cr, while low degree of contamination was seen for Cd, Ni, As, and no degree contamination for V. From the findings of this study, it is therefore important that the water should not be consumed until remediation processes are in order.